Analysis of Data Mining at Supermarket X in Surabaya Using Market Basket Analysis to Determine Consumer Buying Patterns - Akmal Suryadi; Mega Cattleya Prameswari Anissa Islami (Nusantara Science and Technology Proceedings, 2022)
The most common lifestyle change during the Covid-19 pandemic is an increase in people's purchasing power. The strategy that sellers need to pay attention to is product placement. Product placement in stores on a small or large scale is one of the strategies that can affect consumer purchasing decisions. One supermarket in Surabaya experienced an increase in transactions during the pandemic, but there are some products whose sales are not as high as other products due to product placement that is not by the type or function so that when customers want to buy products they have to look for them first, this is not uncommon. customers do not shop or buy products which result in lower transactions and lower supermarket profits. So this research was conducted to provide recommendations for product placement in a layout that suits consumers' wishes, grouping products based on consumer buying habits, and reduce search time. This research was conducted using the Market Basket Analysis (MBA) method. From the results, there are 19 rules which indicate that some products will be purchased if placed close to other products with a 100% confidence level.